Inside Foreign Aid - Tendler, Judith (The Johns Hopkins University Press, 1975)
A classic, important study in the anthropology of development, grounde d in the author's own work within USAID, and analysis of the organizat ional and institutional pressures that constrain and shape development agency employees' cognition and action.
Keywords: IMPORTANT